REGULACJE DOTYCZĄCE ODLEGŁOŚCI MIĘDZY BUDYNKAMI W PRAWACH ANTYCZNYCH - Skalec, Aneta (Zeszyty Prawnicze, 2016)
LEGAL REGULATIONS OF THE DISTANCE BETWEEN THE BUILDINGS IN ANCIENT LAWS Summary Regulations concerning the distance between the buildings can be already found in the law of the XII Tables, which prescribed that 2,5 foots of free space must be left around every house. That space was called ambitus. But most probably, it was the earlier law of Solon in Athens, that served as a model for Romans, and a few centuries later (III BC) was also applied in Dikaiomata – the law of the city of Alexandria in Egypt. As far as the Roman Empire is concerned, we can find series of constitutions issued by imperators, usually concerning the distance between public buildings, and, as regards the fifth century AD, also the distance between private buildings (the most important of them is the constitution of Zenon). This question was an object of interest also for the author of the compilation of local Palestinian laws – Julian of Ascalon, in whose Treatise the problem was regulated in very detailed way. Julian of Ascalon’s Treatise dealt also with the distance between private buildings and many types of workshops.